Assessment of nutritional quality of taro (Colocasia esculenta L. Schott.) genotypes of the Eastern Himalaya, India - Talang, Hammylliende; Mawlong, Gabriella T.; Kjam, Lanamika; Devi, M. Bilashini; Gurung, Bishal; Biswakarma, Niraj; Singh, Nongmaithem Uttam; Verma, Veerendra Kumar; Rymbai, Heiplanmi; Raviteja, Palavalasa; Das, Bapi; Angami, Thejangulie; et al. (Frontiers in Nutrition, 2025)
IntroductionThe eastern Himalayan region of India with diverse agro-climatic conditions is one of the important hotspots of the world’s biodiversity. A wide range of genetic variability of plant species like Colocasia is available in the region which is consumed by the local tribes.Materials and methodsA field study was conducted during 2022–23 to evaluate the yield, biochemical, mineral, and an-tioxidant parameters of 30 Colocasia esculenta L. Schott. genotypes under a split-plot design with three replications.Results and discussionSignificant (p < 0.05) variations were observed among genotypes for all traits. Tamachongkham exhibited the highest corm weight and yield, while Tamitin recorded the maximum cormel weight and total yield. Megha Taro-2 and Megha Taro-1 had the highest cormel numbers and cormel yield, respectively. In mineral composition, Tamitin had the highest N, K, Zn, Cu, and Mn, Tagitung White recorded the highest P, and BCC-2 had the highest Fe and Ca + Mg. Biochemically, Tamachongkham had the highest dry matter content; Khweng-2 had the highest starch, total sugar, and reducing sugar; Rengama had the highest crude protein, and crude fiber; and Mairang Local had the highest ash content. A significant positive correlation was observed between total yield and corm, cormel yield, cormel weight, and corm weight, while correlations with starch and other parameters were non-significant. Total phenolic content and anthocyanin were significantly correlated with Ferric Reducing Antioxidant Power (FRAP). Genotype-by-trait biplot analysis using the first two principal components (PC1: 19.4%, PC2: 14%) high-lighted total sugar, reducing sugar, cormel numbers, crude fiber, anthocyanin, and FRAP as major contributors to phenotypic diversity. The observed variations indicate the potential of these genotypes for future breeding programs aimed at improving taro production in the Eastern Himalayas.